Perceptions of Medical and Dental Doctors on Dealing with ‘Google Informed Patients’ - Abeer Anjum, Remsha Mustafa, Sadia Rana, Khizar Ansar Malik, Shakeel Ahmad, Usman Mahboob, Ayesha Fahim (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To explore the perceptions of the health professionals regarding internet health-seeking behaviour of patients and problems faced by recent medical and dental graduates. Methods: Eight General physicians and six dental surgeons from different regions of Sialkot and seven recent medical and dental graduates were selected via purposive sampling technique. Data was collected through semi-structured interviews over the phone with prior appointments. Manual qualitative thematic analysis was performed by transcribing the interviews and then codes, subthemes, and themes were generated. Results: Six themes and sixteen subthemes were identified depicting the perceptions of physician and problems faced by recent medical and dental graduates, namely: doctor-patient relationship enhanced (due to patients presenting better history, improved communication, and consultations in a healthy environment), Time saved in consultations (makes the task easier, informed patients are helpful and give better results), Threat to patient safety (self-medication, on-compliant to medicines and advices and understanding issues) difficult to counsel(information overload), Frustration (patients stick to conclusions, lack of understanding) and Professional disregard (as patients challenge physician authority, defamation, change their doctors, lack of trust) Conclusion: The theatrical increase of patients’ access to internet health information has caused unpredictable quality impacts on the doctor-patient relationship. Future recommendations have been suggested to overcome the challenges faced by health professionals due to the online searching behaviour of patients and hence improving the health outcomes.